Rzymski hortus jako jeden z symboli miasta nad Tybrem. Krajobraz sepulkralny w przestrzeniach Rzymu od IV w. p.n.e. do I w. n.e. - Dworniak, Justyna (Studia Europaea Gnesnensia, 2016)
The land and its cultivation had an important place in the minds and hearts of people living on the Tiber. As Roman culture developed, there evolved a tradition of building tombs which were to serve the living rather than the dead. This led to a widespread practice of designing “sepulchral landscapes” which became a fixed feature of Rome’s architectural space. Thus the necropolises gained a new function, becoming vibrant parks which offered an ideal locus amoenus